Pemikiran Ibnu Taimiyah dalam Praktek Akad Pembiayaan di Baitul Mal Wat-Tamwil - Udin Saripudin; M Munir Asrori; Suryani Suryani (Jurnal Ilmiah Ekonomi Islam, 2021)
One of Ibn Taymiyah's thoughts (d. 728 H / 1328 AD) that economic transactions are aimed at justice that can only be realized if all the contracts are based on the willingness to agree from all parties, is very interesting to research the practice of financing agreements in Islamic financial institutions (LKS) which in this case Baitul Mal Wat-Tamwil (BMT). The purpose of this study is to find out how much the principle of justice is the basis for the implementation of the financing contract for the parties to the contract. The study uses qualitative methods with a descriptive analysis approach. The research was conducted at BMT Tumang, one of the national-scale BMTs that has contributed to the growth of the sharia microeconomic system. The results showed that Ibn Taymiyah's thoughts regarding the foundation of morality and justice had been applied in the financing agreement at BMT Tumang, it was stated in the Operational Management Standards (SOM) and Standard Operating Procedure (SOP) of BMT Tumang. Keywords : Ibnu Taimiyah, financing agreement, moral foundation, justice, BMT Tumang.